2023
DOI: 10.3390/ani13030353
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Potential Genes and Economic Parameters Associated with Growth and Heat Tolerance in Sheep (Ovis aries)

Abstract: This study explored the potential genes and economic factors that might be associated with growth and heat tolerance in two sheep breeds. Data on growth performance from the third month to six months of age were obtained based on records. In comparison to Aboudeleik lambs, Barki lambs developed considerably greater starting body weight, final body weight, final body weight gain, daily weight gain, and percentage increase in BW/month. Single nucleotide polymorphisms (SNPs) were found between lambs of the two br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The sympathoadrenal and hypothalamus-pituitary-adrenal (HPA) axes are crucial in the implementation of the action of stress factors (Bagath et al 2019). Recent studies have suggested that catecholamines alter the number and function of lymphocytes exerting an inflammatory effect, while cortisol causes a decrease in the immune system of animals (Ibrahim et al 2023). It has been shown that stress worsens the immune response and causes immunosuppressive effects (Chen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The sympathoadrenal and hypothalamus-pituitary-adrenal (HPA) axes are crucial in the implementation of the action of stress factors (Bagath et al 2019). Recent studies have suggested that catecholamines alter the number and function of lymphocytes exerting an inflammatory effect, while cortisol causes a decrease in the immune system of animals (Ibrahim et al 2023). It has been shown that stress worsens the immune response and causes immunosuppressive effects (Chen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These genetic markers, or SNPs, can be used to identify the genetic variation that underlies traits in livestock animals that are economically significant and to better understand how genetic variants connect to various phenotypes (Daw et al, 2005). In order to make it easier to choose breeding animals that will actually improve traits connected to growth, genetically based improvement programs should be created (Ibrahim et al, 2023).…”
Section: Introductionmentioning
confidence: 99%